Partial purification and characterization of Cellulase-free xylanase production from bacillus licheniformis - SARIKA CHATURVEDI; SM PAUL KHURANA (International Journal of Pharma and Bio Sciences, 2016)
A new isolate of Bacillus licheniformis SC produced extracellular xylanase when grown on 3% wheat bran, without xylanase multiplicity. The enzyme was partially purified by ammonium sulphate and gel filtration using Sephadex G-100 column. The purified xylanase showed optimum pH at 8.0 and half maximum activity at pH 4.5. The pH stability profile showed that it was more stable in the pH range of 6 to 8. Its activity increased with rise in temperature and maximum upto 600C. The molecular mass for xylanase was 24.6 kDa respectively. The SDS-PAGE of the purified xylanase migrated as a single band. The Km was found to be 4.8 g/ml and the Vmax was 0.58 μmol/minute/ml for xylanase. In addition, the present xylanase was capable of producing high-quality xylo-oligosaccharides, indicating its application potential for biobleaching processes of pulp.